Knowledge, attitude and practice of adverse drug reaction monitoring and reporting among nurses of secondary healthcare - MN, Sachidananda Adiga; Banavalikar, Nandth Poornanand (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADRs) are responsible for significant morbidity and mortality. Nurses will play a vital role in monitoring and reporting of ADRs. Hence this study was conducted to assess the knowledge, attitude and practice of adverse drug reaction monitoring and reporting among secondary healthcare level. Methods: In this questionnaire based study, 98 nurses working in district hospital Karwar (a secondary level healthcare facility) were grouped according to their working experience. Pre-validated questionnaire was distributed to assess the knowledge, attitude and practice of ADR monitoring and practice in their setting. Responses were converted into scores using predetermined scoring method and assessed for their level of knowledge, attitude and practice. Suitable statistical tests were applied to assess the statistical significance. Results: It has been found out that, the knowledge score ranged from 30.52±2.89 to 40.5±2.3 with no statistical significance. The attitude and practice score ranged from 43.33±2.13 to 53.85±2.67 and 23.8±4.17 to 45±7.54 respectively, with the statistical significance of 0.03 and 0.02 respectively between the groups. 72.5% participants had observed at least one ADR, while 45% of them had reported the ADR to higher authority. 82.5% of participants opined that there should be frequent awareness programs to update their knowledge on ADRs. Many factors like legal liabilities (14.5%), didn’t know where to report (24.45%), did not think reporting ADR was important (5%), non-availability of ADR reporting forms (31%) were some of discouraging factors for non -reporting of ADRs. Conclusions: We conclude from our study that even though knowledge about ADRs was relatively better despite being a resource limited setting, the attitude and practice of reporting of drug reactions needs to be improved.